Preventing non-contact ACL injuries in female athletes: What can we learn from dancers? - Turner, C.; Crow, S.; Crowther, T.; Keating, B.; Saupan, T.; Pyfer, J.; Vialpando, K.; Lee, S.-P. (Physical Therapy in Sport, 2018)
Objectives:To investigate the effects of dance experience and movement instruction on lower extremity kinematics and muscle activation during a landing task. Design: Cross-sectional case control. Setting: Laboratory setting. Participants: 27 female subjects (age 18-25) in 2 groups: dancers (n=12) and non-dancers (n=15). Main outcome measures: Lower extremity biomechanics during drop landing were analyzed. Subjects performed drop landings after watching an instructional video without verbal instructions (NI), followed by repeat assessment after watching the same videos with specific verbal instructions (VI). Surface electromyography (EMG) was used to measure the activation of gluteus maximus and medius during the deceleration phase of landings. Peak knee and hip frontal plane angles during landing were acquired using a 3-D motion capture system. Results:; Compared to non-dancers, dancers demonstrated generally greater gluteus maximus activation and a decreased knee abduction (i.e. valgus) angle during drop landing. A significant interaction showed that instruction led to increased knee valgus angle in non-dancers but not dancers (p=.014). Conclusions: Our findings suggest that experienced dancers demonstrate safer landing strategies compared to recreational athletes. Providing acute movement instruction was shown to disrupt the landing mechanics in those with no dance training experience.